Effect of echocardiography on prognosis in patients with type 2 diabetes mellitus - Zhi Jiang; Jing-hui Chen; Ling-jie Zhang; You-ping Zheng; Si-hua Qiu (PLoS ONE, 2025)
Objective There was a lack of studies on the relationship between the presence or absence of echocardiography and the prognosis of type 2 diabetes mellitus (DM) patients. Therefore, we used the Medical Information Mart for Intensive Care (MIMIC)-IV database to explore the relationship between them. Method The patient information was obtained from the MIMIC-IV database. Taking age, BMI, sex, race, and marital status as scoring items, Propensity Score Matching was carried out according to the ratio of 1: 1. Generalized linear regression, multivariate logistic regression and hierarchical analysis were used to analyze the correlation between echocardiography and prognosis in type 2 DM patients. Results A total of 9140 patients were enrolled in this study. There were differences in body mass index, days of type 2 DM, estimation of glomerular filtration rate, length of stay, survival time, readmission, marital status, family history of type 2 DM, drinking, smoking, metformin, coronary heart disease, heart failure, arrhythmia, hypertension, hyperlipidemia, cardiomyopathy, myocardial infarction, atherosclerosis, epilepsy, and thyroid diseases between patients with echocardiography and those without echocardiography. Echocardiography was independently related to survival time and readmission in type 2 DM patients. Besides, echocardiography was related to the survival time of patients with type 2 DM without complications. Conclusions We found for the first time that echocardiography was independently associated with the survival time of type 2 DM patients without complications.